Perbedaan Hasil Belajar Matematika Menggunakan Model Pembelajaran Student Team Achievment Division (STAD) dengan Two Stay Two Stray (TSTS) kelas X IPA - Riza Agustiani; Rima Dwi Kemala; Rieno Septra Niery (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to determine the differences in learning outcomes of mathematics using the Student Team Achievement Divisionn (STAD) learning model with the Two Stay Two Stray (TSTS) learning model for students of class X IPA MAN 01 OKU. This type of research is a quantitative research with nonequivalent control group design. The experimental class was taken based on the results of the pre-test. Students are divided into two categories, namely high-ability students and low-ability students. The data analysis technique in this study used the t-test with the help of SPSS. Based on the results of the study, with a significant value of 0.022 for high-ability students, 0.00 for low-ability students and 0.017 for the whole class. The average value of the STAD class is 74.24 and the TSTS class is 60.00. This means that the Student Team Achievement Divisionn (STAD) cooperative learning model is better than using the Two Stay Two Stray (TSTS) cooperative learning model.